2013
DOI: 10.1155/2013/916370
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Low-Level Laser Therapy on Hearing

Abstract: One purported use of low-level laser therapy (LLLT) is to promote healing in damaged cells. The effects of LLLT on hearing loss and tinnitus have received some study, but results have been equivocal. The purpose of this study was to determine if LLLT improved hearing, speech understanding, and/or cochlear function in adults with hearing loss. Using a randomized, double-blind, placebo-controlled design, subjects were assigned to a treatment, placebo, or control group. The treatment group was given LLLT, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 20 publications
(19 reference statements)
0
19
0
2
Order By: Relevance
“…In the 1990s, He-Ne and Ga-Al-As lasers operating at 632 and 904 nm were used to this end [73][74][75][76][77][78]. Most studies reported positive effects [73,74,76,77] but two using a similar [75] and a different [78] laser [86] did not. PBM therapy, at least weekly, at a wavelength of 630-900 nm and an average power of 20 mW, improved tinnitus.…”
Section: Previous Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1990s, He-Ne and Ga-Al-As lasers operating at 632 and 904 nm were used to this end [73][74][75][76][77][78]. Most studies reported positive effects [73,74,76,77] but two using a similar [75] and a different [78] laser [86] did not. PBM therapy, at least weekly, at a wavelength of 630-900 nm and an average power of 20 mW, improved tinnitus.…”
Section: Previous Human Studiesmentioning
confidence: 99%
“…Shiomi et al [79] were the first to use a PBM diode laser to treat tinnitus; 58% of patients reported loudness reductions and 55% less annoyance. Later studies used PBM diode lasers to treat tinnitus [80][81][82][83][84], hyperacusis [85], and poor hearing [86]. Any effect of PBM remains controversial.…”
Section: Previous Human Studiesmentioning
confidence: 99%
“…In Iowa, a double-blind, placebo-controlled trial was conducted that evaluated the effect of laser therapy on hearing functions [86]. 30 patients were randomly assigned to 3 groups and either treated with low level laser (n=9), with placebo (n=10), or not at all (n=10).…”
Section: Neuromodulation – Instrument-based Medical Interventionsmentioning
confidence: 99%
“…Nas últimas duas décadas, o laser de baixa intensidade foi introduzido para a proteção das células ciliadas do ouvido interno contra traumas, uma vez que acadêmicos presumem que a TLBI pode melhorar a função coclear (GOODMAN et al, 2013;MOON et al, 2016). Embora o mecanismo exato do efeito da fotobiomodulação no zumbido não seja claramente compreendido, tem sido proposto que seus efeitos podem ser induzidos pelo aumento da proliferação celular, melhora no fluxo sanguíneo da orelha interna e/ou ativação das mitocôndrias das células ciliadas (OKHOVAT et al, 2011;MOLLASADEGHI et al, 2013 (TAUBER et al, 2000;CHAVANTES, 2008;AILIOAIE et al, 2014;MOON et al, 2016).…”
Section: Grupounclassified
“…Um estudo realizado por Salahaldin et al (2012) Quando fala-se de zumbido e fotobiomodulação aplicado aos seres humanos, diversos resultados, tanto positivos (TAUBER et al, 2003;OKHOVAT et al, 2011;MOLLASADEGHI et al, 2013;DEMIRKOL et al, 2017), quanto negativos (TEGGI et al, 2009;GOODMAN et al, 2013;NGAO et al, 2013;DEHKORDI et al, 2015) são encontrados na literatura internacional. Padronizar medidas melhora a comparabilidade dos resultados do tratamento entre os diferentes tipos intervenções e centros de tratamento, facilita a integralidade das alternativas de intervenção…”
Section: Grupounclassified